2018
DOI: 10.1080/00405000.2018.1532780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotor spinning transfer channel modification on fiber orientation and yarn properties

Abstract: The vortices are generated at the conventional transfer channel, having adverse effects on fiber configuration. In a former research, a conventional transfer channel was modified via rounding the transfer channel inlet corner and adding a bypass channel. The simulation results obtained with the modified transfer channel showed that the vortices were eliminated and the inlet air velocity increased. We present the impact of this modification on the yarn properties and fiber straightness. Four groups of yarn samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…During the yarn formation process, the vortices generated at the dust-removing channel are not conducive to the discharge of impurities, and the impurities easily flow back, resulting in a higher impurity rate of the yarn. 10,11 Dust content is the main factor affecting yarn strength. The higher the trash content, the lower the breaking strength of the yarn, the higher the nonuniformity of the breaking strength, and the lower the quality of the yarn.…”
Section: Performance Discussion and Simulation Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the yarn formation process, the vortices generated at the dust-removing channel are not conducive to the discharge of impurities, and the impurities easily flow back, resulting in a higher impurity rate of the yarn. 10,11 Dust content is the main factor affecting yarn strength. The higher the trash content, the lower the breaking strength of the yarn, the higher the nonuniformity of the breaking strength, and the lower the quality of the yarn.…”
Section: Performance Discussion and Simulation Verificationmentioning
confidence: 99%
“…10 It was also reported that lower rotor velocity can cause more vortices, but too high a rotor velocity can lead to an increase in yarn breakages due to the centrifugal force. 11 In this study, two accurate computational fluid dynamics (CFD) models of rotor spinning machines with different types of carding and dust-removing chambers were developed. The airflow behavior, air pressure, and turbulent energy of the two chambers were simulated and comprehensively compared based on the developed CFD simulation models and the yarns produced with the two chambers.…”
mentioning
confidence: 99%
“…Seyedi et al 14 utilized the tracer fiber technique to investigate and analyze the fiber migration in the airflow field of newly rotor-jet spun yarn with the rotor-jet spinning parameters varying. Seyed et al 15 and Lin et al 16 carried on the spinning test to compare the yarn quality and hence verified the effect of the optimized transfer channel airflow field on the yarn properties. Akankwasa et al 17 also evaluated the blended yarn quality to support the simulated results of the airflow characteristics in conventional and dual-feed rotor spinning machines.…”
mentioning
confidence: 90%
“…15 and Lin et al. 16 carried on the spinning test to compare the yarn quality and hence verified the effect of the optimized transfer channel airflow field on the yarn properties. Akankwasa et al.…”
mentioning
confidence: 91%
“…In the study by Akankwasa et al, 11 the transfer channel was modified so that the top and side walls extended 16 mm above the waste discharge chute, thereby reducing fiber jitter on the outer wall of the channel and limiting fiber displacement in front of the channel inlet. Lin et al 12 conducted an experimental study of the transfer channel and used cluster analysis to derive an optimum design for the transfer channel. They suggested either increasing the transmission channel inlet air velocity or reducing the channel inlet size, both in favor of fiber straightening.…”
mentioning
confidence: 99%